A conjugate of the lytic peptide Hecate and gallic acid: structure, activity against cervical cancer, and toxicity - Sanches, Paulo Ricardo da Silva [UNESP]; Carneiro, Bruno Moreira [UNESP]; Batista, Mariana Nogueira [UNESP]; Braga, Ana Claudia Silva [UNESP]; Lorenzon, Esteban Nicolás [UNESP]; Rahal, Paula [UNESP]; Cilli, Eduardo Maffud [UNESP] (Springer, 2015)
Conjugate compounds constitute a new class of molecules of important biological interest mainly for the treatment of diseases such as cancer. The N-terminus region of cationic peptides has been described as important for their biological activity. The aim of this study was to evaluate the lytic peptide Hecate (FALALKALKKALKKLKKALKKAL) and the effect of conjugating this macromolecule with gallic acid (C7H6O5) in terms of structure, anti-cancer activity, and toxicity. An N-terminus GA-Hecate peptide conjugate was synthesized to provide information regarding the relationship between the amino-terminal region and its charge and the secondary structure and biological activity of the peptide; and the effects of gallic acid on these parameters. Peptide secondary structure was confirmed using circular dichroism (CD). The CD measurements showed that the peptide has a high incidence of alpha-helical structures in the presence of SDS and LPC, while GA-Hecate presented lower incidence of alpha-helical structures in the same chemical environment. An evaluation of the anti-cancer activity in HeLa cancer cells indicated that both peptides are active, but that coupling gallic acid at the N-terminus decreased the activity of the free peptide. GA-Hecate showed lower activity in non-tumor keratinocyte cells but higher hemolytic activity. Our findings suggest that the N-terminus of Hecate plays an important role in its activity against cervical cancer by affecting it secondary structure, toxicity, and hemolytic activity. This study highlights the importance of the N-terminus in antitumor activity and could provide an important tool for developing new anti-cancer drugs.
Keywords: Hecate; Gallic acid; Bioconjugates; Cervical cancer; Hemolytic activity; Secondary structure